Idiotype profile of an immune response. I. Contrasts in idiotypic dominance between primary and secondary responses and between IgM and IgG plaque- forming cells - Conger, JD (The Rockefeller University Press, 1981)
The primary response of A/J mice to p-azobenzenearsonate-keyhole limpet hemocyanin (ABA-KLH) was investigated. A day-by-day analysis at the plaque- forming cell (PFC) level was performed, with inhibition by anti-cross- reactive idiotype (CRI) serum to determine percentage of CRI(+) PFC. A regular pattern in the dynamics of Id (idiotype) dominance was observed. Just as in the NP-b and NP-a systems (9, 12), the major Id (CRI) is more dominant in primary than in secondary or hyperimmune responses. This trend is more apparent in IgG PFC which are generally 80-95 percent CRI(+) at day 10 in the primary response but only 30-40 percent CRI(+) at day 10 in secondary or hyperimmune responses. A somewhat different pattern is seen with IgM PFC. These may reach a peak of 85 percent CRI(+) in the primary response, but secondary or hyperimmune IgM PFC, which are lower in numbers than IgG PFC, remain high in CRI content at approximately 70 percent. The PFC data on extent of id dominance in secondary or hyperimmune responses is fully compatible with previously reported serological data by others. Analysis of IgG PFC by hapten inhibition indicated that heterogeneity was in the order secondary PFC {greater than} primary PFC {greater than} hybridoma AK-2.2 PFC with H(75)/H(25) values of 22.9, 6.2, and 2.7, respectively; where H(75) and H(25) are the hapten concentrations required to give 75 percent and 25 percent of inhibition of PFC, respectively. Hapten inhibition data also suggested that secondary IgG PFC were 10 times higher in median binding avidity for ABA-L-tyrosine than primary IgG PFC. The kinetic analysis strongly indicated that CRI(+) IgM PFC were preferentially switched to IgG PFC in the primary response. In both studies, the CRI content of the earliest-appearing IgG PFC was significantly higher than that of IgM PFC on that day. For example, in one case IgM PFC were 60 percent CRI + on day 6 whereas IgG PFC were 100 percent CRI(+). The high Id dominance and selective isotype switching may have either a B or a T cell basis.